1995
DOI: 10.2307/1382621
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fluorescent Pigments in Studies of Seed Caching by Rodents

Abstract: We describe a new technique for locating seeds cached by rodents that offers practical and logistical advantages over previous methods. The new technique uses ultraviolet illumination and seeds marked with powdered fluorescent pigments, which transfer readily between surfaces upon contact and have been applied successfully for other research on small mammals. We used the technique at a field site in the Great Basin Desert of western Nevada to test and verify the prediction that seed-caching, heteromyid rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…Thus, the hypotheses above are seldom tested under field conditions based on observations of the relationship between seeds and rodents at individual level (but see Jansen et al 2012). Traditional methods to track seed dispersal, including direct observation (Morris 1962;Stapanian & Smith 1978), metal marking (Sork 1984), thread marking (Forget 1990), fluorescent marking (Longland & Clements 1995;Levey & Sargent 2000), radioactive isotope marking (Lawrence & Rediske 1960;Abbott & Quink 1970;Hollander & Vander Wall 2004) and wire tin/plastic-labelled seed tagging (Zhang & Wang 2000;Xiao et al 2008), are not able to distinguish individual seed dispersers. Recently, a method combining very high frequency (VHF) radio transmitter and infrared radiation (IR) camera tracking was proposed by Jansen et al to identify both the seed dispersers and seed fates, and to calculate the rates of pilferage of seeds (such as Astrocaryum standleyanum, weighing approximately 10 g) dispersed by rodent species (such as Dasyprocta punctata (Gray, 1842), weighing approximately 2 to 4 kg); the results indicated that the pilferage was very common (Jansen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the hypotheses above are seldom tested under field conditions based on observations of the relationship between seeds and rodents at individual level (but see Jansen et al 2012). Traditional methods to track seed dispersal, including direct observation (Morris 1962;Stapanian & Smith 1978), metal marking (Sork 1984), thread marking (Forget 1990), fluorescent marking (Longland & Clements 1995;Levey & Sargent 2000), radioactive isotope marking (Lawrence & Rediske 1960;Abbott & Quink 1970;Hollander & Vander Wall 2004) and wire tin/plastic-labelled seed tagging (Zhang & Wang 2000;Xiao et al 2008), are not able to distinguish individual seed dispersers. Recently, a method combining very high frequency (VHF) radio transmitter and infrared radiation (IR) camera tracking was proposed by Jansen et al to identify both the seed dispersers and seed fates, and to calculate the rates of pilferage of seeds (such as Astrocaryum standleyanum, weighing approximately 10 g) dispersed by rodent species (such as Dasyprocta punctata (Gray, 1842), weighing approximately 2 to 4 kg); the results indicated that the pilferage was very common (Jansen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative tagging methods for tracking seed dispersal by animals include radioisotopes (Carlo et al 2009;Vander Wall 2002a, b;Winn 1989), fluorescent dye (Lemke et al 2009;Longland and Clements 1995), and metal or magnets . A limitation of the above methods is that seeds dispersed over longer distances are less likely to be retrieved because search effort increases exponentially with search radius.…”
Section: Introductionmentioning
confidence: 99%
“…(d) Seed predation and dispersal by nocturnal rodents To compare the initial fates of seeds removed by nocturnal rodents, we used fluorescent seed tracking (Longland & Clements 1995;Tomback et al 2005) combined with a reciprocal transplant experiment using seeds from areas with (mean seed coat thicknessZ0.35G0.0006 mm (s.e.)) and without (mean seed coat thicknessZ0.16G0.0005 mm) red squirrels (thick and thin seed coats, respectively) in both areas with and without red squirrels.…”
Section: Methodsmentioning
confidence: 99%